Lead-Free Electronic Solders A Special Issue of the Journal of Materials Science: Materials in Electronics - Subramanian, KV (Springer US : Imprint: Springer, 2007)
In the last few decades the effect of lead contamination on human health has received significant attention. Based on such concerns, elimination of lead from ceramic glaze, paint, plumbing etc. has been legislated and implemented. However, until recently, solders used in electronics, based on suitability and knowledge-base developed over a long period of time, remained lead-based. Successive rapid advances in microelectronic devices in recent decades make them obsolete within a very short period after their introduction resulting in significant quantities of electronic wastes in landfills. Leaching of toxic lead from such electronic wastes can result in contamination of the human food chain causing serious health hazards. As a consequence, several European and Pacific Rim countries have passed legislations warranting elimination of lead from electronic solders by fast approaching deadlines. Global economic pressures brought on by such legislations have resulted in a flurry of research activities to find suitable lead-free substitutes for the traditional leaded electronic solders. The worldwide multi-faceted research efforts to arrive at suitable solutions, especially as the deadline for implementation of lead-free electronic solders approaches, have resulted in an exhaustive number of research papers in several reviewed scientific journals. Similarly there have been presentations in several national and international meetings of various technical societies. It is impossible for any researcher or student to be aware of all the materials that have been, and are being, published in this area. So it becomes essential to have most of the relevant and currently available information in a single source. With this goal in mind, the important issues that are encountered in the lead-free electronic solder area were identified, and researchers recognized for their significant scientific contributions in those areas, were invited to write articles on those topics. They were asked to address the importance of a given issue, the current status of understanding and available solutions, the problems that still need to be tackled and suggestions for potential approaches to do so. This book contains the papers that were invited for a special issue of Journal of Electronic Materials: Materials in Electronics. Because this journal may not be a regular source of scientific information for academic researchers in fields other than Materials Science and those in industry, and to provide wider awareness of the current status of lead-free electronic solders to those persons active in the area but who are not regular readers of the Journal, these articles have been reprinted in this book.